Effects of an 8-week pilates core training on the stability and symmetry of the l-sit on rings - Gil, H.; Yoo, S.; Yoon, S. (Korean Journal of Sport Biomechanics, 2016)
Objective: Gymnastics on rings needs a high level of muscle strength with balance ability for controlling the body. A study on a new balance training program is necessary for elite gymnasts. Therefore, the purpose of this study was to investigate the effects of an 8-week pilates core-muscle training on balance ability and asymmetry index of the L-sit on the rings in male elite gymnasts. Method: Ten elite gymnasts (age: 20.6±0.7 years, height: 169.9±4.9 cm, weight: 65.4±5.6 kg, career duration: 20.6±0.7 years), who are students at K-university, participated in this study. Results: First, the range of the COM tended to decrease in the anterior-posterior direction. Second, the left hip joint angle and knee extension and ankle dorsiflexion angles significantly increased after the pilates training. Third, the ROM also increased. Fourth, the symmetry value increased in the hip angle, while the symmetry index in all joints of the ROM decreased. As a result, the pilates core-muscle training influenced the static balance ability during the L-sit on the rings. Conclusion: Accordingly, the pilates core-muscle training is suitable in enhancing the basic balance ability in gymnastics on rings.